Transparent chitosan films reinforced with a high content of nanofibrillated cellulose - Fernandes, Susana C.M.
This paper reports the preparation and characterization of nanocomposite films based on different chitosan matrices and nanofibrillated cellulose (NFC) for the purpose of improving strength properties. The nanocomposite films were prepared by a simple procedure of casting a water-based suspension of chitosan and NFC, and were characterized by several techniques: namely SEM, X-ray diffraction, visible spectrophotometry, TGA, tensile and dynamic-mechanical analysis. The films obtained were shown to be highly transparent (transmittance varying between 90 and 20% depending on the type of chitosan and NFC content), flexible, displayed better mechanical properties, with a maximum increment on the Young's modulus of 78% and 150% for high molecular weight (HCH) and water-soluble high molecular weight (WSHCH) filled chitosans, respectively; and of 200% and 320% for low molecular weight (LCH) and water-soluble filled (WSLCH) chitosans, respectively. The filled films also showed increased thermal stability, with, for example, an increase in the initial degradation temperature (Td(i)) from 227 degrees C in the unfilled LCH film up to 271 degrees C in filled LCHNFC50% nanocomposite films, and a maximum degradation temperature (Tdi) raising from 304 degrees C to 313 degrees C for the same materials. (C) 2010 Elsevier Ltd. All rights reserved.